Isolation and identification of an AKAV strain in dairy cattle in China - Miaomiao Zhang; Menghua Deng; Sisi Zhao; Dengshuai Zhao; Yajie Zheng; Limei Qin; Han Gao; Mengmeng Zhao; Keshan Zhang (Frontiers in Veterinary Science)
Akabane disease is an arthropod-borne disease caused by Akabane virus (AKAV), which is characterized by abortion, premature birth, stillbirth, congenital arthrosis, and hydrocephalic anencephalic syndrome in pregnant cattle and sheep. The occurrence of AKAV was proved by RT-PCR amplification based on AKAV S fragment, virus isolation, cells inoculation, cytopathy, transmission electron microscopy, and gene sequencing. The PCR amplicon was approximately 850 bp and was sequenced, and molecular identification of AKAV was conducted through phylogenetic analysis of S gene sequence. The results indicated that AKAV isolated from cattle in this study was genetically close to the strain isolated from Rhizomys pruinosus in China in 2016. However, the outbreak in bamboo rats may have been a sporadic event. The probability that Akabane virus (AKAV) can spread in rodents and mammals is still uncertain and requires further investigation. Using transmission electron microscopy (TEM), AKAV particles displayed the typical morphology associated with bunyaviruses reported previously. In brief, the AKAV infection in cattle has been confirmed. This case report highlights the necessity for enhanced surveillance and preventive measures to mitigate the potential impact on livestock health and productivity.